HERITABILITY, VARIANCE COMPONENTS AND GENETIC ADVANCE OF GARRI QUALITY TRAITS IN CASSAVAVARIETIES CULTIVATED IN OKUKU OWERRI-WEST SOUTHEASTERN, NIGERIA (Wudil Journal of Science and Technology Education, 2025)
The experiment was conducted at the Center for Agricultural Research, School of Agricultureand Agricultural technology of the Federal University of Technology Owerri, Imo State,Nigeria between January, 2023 – January, 2024 to estimate the heritability, variancecomponents and genetic advance as the percentage of the mean of garri quality traits incassava varieties cultivated in Okuku (Okuku locals) along some improved varieties. Threelocal varieties were sourced from a subsistence farmer in Okuku, Owerri-West, Imo State andfive improved varieties were sourced from National Root Crop Research Institute (NRCRI),Umudike, Abia State. Each cassava variety was planted in a 12x1m (12m2).plot size at aplanting distance of 1mx1m. The experiment was laid out in a Randomized Complete BlockDesign (RCBD) with four replications. Cassava stem cuttings of about 20cm with at leastfour nodes were planted on ridges, at 48 weeks after planting; the eight cassava varietieswere harvested and processed into garri. The garri quality traits were grouped into:functional properties, proximate composition and minerals composition. Data were collectedon swelling index(%), bulk density(g/ml), water absorption capacity(%), moisturecontent(%), ash(%), dietary fiber(%), crude fat(%), crude protein(%), carbohydrate(%),calcium(%), sodium(%), phosphorus(%) and potassium(%). Data collected were subjected toanalysis of variance (ANOVA) and means separation was done using Least SignificantDifference (LSD). The Analysis of Variance showed significant differences (p < 0.05) amongthe cassava varieties evaluated. Nwajeni and TMS 164773 exhibited higher protein, swellingindex, and mineral contents, and so, may be preferred for nutritional and functional quality.Conversely, IBA980505 with lower moisture content and higher carbohydrate may befavored for shelf stability and energy yield. Genetic parameters such as mean, range,coefficient of variation, variances, heritability in broad-sense and genetic advance as thepercentage of the mean were estimated for the 13 different traits. The study demonstratedthat the observed variation was predominantly genetic in nature for most traits. Heritabilityvalues range from 35.90 – 100. 43Traits with the highest Genetic Advance as Percentage ofMean (GAM) were Ash (145.45%), Calcium (Ca) (122.22%), Crude Fiber (CFr) (45.45%),and Crude Fat (CF) (44.28%)., the combination of high heritability and high genetic advancefor traits like Ash, Ca, CF, and CFr suggests that direct phenotypic selection remains themost efficient and rapid approach to improving key garri quality attributes
Keywords: heritability, genetic, garri, cassava, traits, varieties